(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aims to identify the level of cognitive beliefs, as well as to identify the level of self-organized learning strategies among intermediate school students. The study also aims to identify the differences in the level of self-organized learning strategies among intermediate school students in term of gender, branch (scientific, literary). In order to achieve the research objectives, the researcher designed a scale to measure the cognitive beliefs. As for the scale of self-organized learning strategies, the researcher adopted a scale of (Pintrich et al. 1991), which was translated by (Izzat Abdelhamid, 1999) , For self-organized learning strategies, the sample consisted of (400) students from the research population, which were randomly selected from the preparatory stage / morning study. The results showed that intermediate school students have cognitive beliefs; the level of self-organized learning strategy is statistically significant compared to the cognitive beliefs. Moreover, males are more capable of self-organized learning than females; individuals with scientific disciplines are more capable of self-organized learning strategies compared to human subjects. Finally, there is no statistically significant difference in the interaction between gender and the study specialization at the level of cognitive beliefs.